Rapid ESKAPE pathogens detection method using tapered dielectrophoresis electrodes via crossover frequency analysis - Muhammad Khairulanwar Abdul Rahim; Nur Mas Ayu Jamaludin; Jacinta Santhanam; Azrul Azlan Hamzah; Muhamad Ramdzan Buyong (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper introduces the versatile of an electrokinetic technique by using the non-uniform electric field for dielectrophoresis (DEP) application. This technique is defined as electromicrofluidics. The potential application for portable and real time detection method of Enterococcus faecium (EF), Staphylococcus aureus (SA), Klebsiella pneumoniae (KP), Acinetobacter baumannii (AB), Pseudomonas aeruginosa (PA) and Enterobacter aerogenes (EA), which are the (ESKAPE) bacteria. The MATLAB analytical modelling was used in simulating the polarisation factor and velocities of bacteria based on Clausius-Mossotti factor (CMF). The validation of CMF simulation through the DEP experimental can be quantified based on the response of alternating current (AC) voltage applied using 6 voltage peak to peak (Vp-p) to their input frequencies from 100 to 15000 kHz. The droplet method was deployed to place properly 0.2 μL of sample onto DEP microelectrode. The velocities and crossover frequency (fxo) ranges of bacteria were determined through bacteria trajectory in specific time interval monitored by microscope attached with eyepiece camera. The applied range of input frequencies from 100 to 15000 kHz at 6 Vp-p for each bacteria were successfully identified the unique ranges of frequencies response for detection application. The advantages of this works are selective with rapid capability for multidrug resistant (MDR) bacteria detection application.